Responses of differential metabolites and pathways to high temperature in cucumber anther - Chen, Lin; Liang, Zhaojun; Xie, Shuyan; Liu, Wenrui; Wang, Min; Yan, Jinqiang; Yang, Songguang; Jiang, Biao; Peng, Qingwu; Lin, Yu’e (Frontiers in Plant Science, 2023)
Cucumber is one of the most important vegetable crops, which is widely planted all over the world. Cucumber always suffers from high-temperature stress in South China in summer. In this study, liquid chromatography–mass spectrometry (LC-MS) analysis was used to study the differential metabolites of cucumber anther between high-temperature (HT) stress and normal condition (CK). After HT, the pollen fertility was significantly reduced, and abnormal anther structures were observed by the paraffin section. In addition, the metabolomics analysis results showed that a total of 125 differential metabolites were identified after HT, consisting of 99 significantly upregulated and 26 significantly downregulated metabolites. Among these differential metabolites, a total of 26 related metabolic pathways were found, and four pathways showed significant differences, namely, porphyrin and chlorophyll metabolism; plant hormone signal transduction; amino sugar and nucleotide sugar metabolism; and glycine, serine, and threonine metabolism. In addition, pollen fertility was decreased by altering the metabolites of plant hormone signal transduction and amino acid and sugar metabolism pathway under HT. These results provide a comprehensive understanding of the metabolic changes in cucumber anther under HT.